2018
DOI: 10.1136/heartjnl-2018-313415
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of His bundle pacing in patients with heart failure with left bundle branch block

Abstract: pHBP improved LVEF, LVESV and NYHA Class in patients with HF with typical LBBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
251
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(266 citation statements)
references
References 22 publications
9
251
2
4
Order By: Relevance
“…As traditional right ventricular (RV) pacing has been found to increase the risk of decreased quality of life, heart failure, and atrial fibrillation in patients who need frequent pacing, physiological pacing has been pursued in the last decade. His bundle pacing (HBP), which utilizes the native cardiac conduction system, is physiological and has demonstrated clinical benefits in bradycardia and even patients with heart failure . However, HBP has some limitations, such as operational difficulty with relatively long fluoroscopic exposure times and sometimes high and unstable pacing capture threshold .…”
Section: Introductionmentioning
confidence: 99%
“…As traditional right ventricular (RV) pacing has been found to increase the risk of decreased quality of life, heart failure, and atrial fibrillation in patients who need frequent pacing, physiological pacing has been pursued in the last decade. His bundle pacing (HBP), which utilizes the native cardiac conduction system, is physiological and has demonstrated clinical benefits in bradycardia and even patients with heart failure . However, HBP has some limitations, such as operational difficulty with relatively long fluoroscopic exposure times and sometimes high and unstable pacing capture threshold .…”
Section: Introductionmentioning
confidence: 99%
“…HBP can normalize LBBB in some patients and thus potentially replace biventricular pacing for cardiac resynchronization therapy . Moreover, recent clinical studies have reported high success rates (up to 90%) for correction of LBBB by HBP . This finding suggests that conduction block of the LBB occurs in the proximal portion of the His‐Purkinje system in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the present investigation, the lead tip position under the TVA did not affect tricuspid valve function during the follow‐up period, probably due to the small‐diameter pacing lead sitting between the septal leaflet and the anterior leaflet of the tricuspid valve. Thus, the advantage of this technique is to reveal a specific location for HBP, likely making the HBP implantation predictable, especially for vHBP that has recently been thought to be a better HBP option with a low and stable capture threshold, high R‐wave amplitude for pacing management, and the capability to correct left bundle branch block …”
Section: Discussionmentioning
confidence: 99%